2022
DOI: 10.3389/fmed.2022.820544
|View full text |Cite
|
Sign up to set email alerts
|

Real-Word Effectiveness of Global COVID-19 Vaccines Against SARS-CoV-2 Variants: A Systematic Review and Meta-Analysis

Abstract: BackgroundCurrently, promoted vaccinations against SARS-CoV-2 are being given out globally. However, the occurrence of numerous COVID-19 variants has hindered the goal of rapid mitigation of the COVID-19 pandemic by effective mass vaccinations. The real-word effectiveness of the current vaccines against COVID-19 variants has not been assessed by published reviews. Therefore, our study evaluated the overall effectiveness of current vaccines and the differences between the various vaccines and variants.MethodsPu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 114 publications
(241 reference statements)
3
28
0
Order By: Relevance
“…However, it is currently unknown if this improvement is limited to the vaccine-matched Omicron VOC. Our data support real-world evidence studies on vaccine effectiveness, 30,59,60 that demonstrated that boosting with the original Wuhan S protein based vaccines continues to provide robust protection from severe COVID-19 disease and hospitalization due to SARS-CoV-2 VOC infections.…”
Section: Discussionsupporting
confidence: 78%
“…However, it is currently unknown if this improvement is limited to the vaccine-matched Omicron VOC. Our data support real-world evidence studies on vaccine effectiveness, 30,59,60 that demonstrated that boosting with the original Wuhan S protein based vaccines continues to provide robust protection from severe COVID-19 disease and hospitalization due to SARS-CoV-2 VOC infections.…”
Section: Discussionsupporting
confidence: 78%
“… 1 Nonetheless, vaccines seem unable to fully reduce the spread of SARS-CoV-2 variants of concerns (VOCs). 2 …”
Section: Introductionmentioning
confidence: 99%
“…1 Nonetheless, vaccines seem unable to fully reduce the spread of SARS-CoV-2 variants of concerns (VOCs). 2 Following the COVID-19 outbreak, leading to hundreds of millions of acute cases and six million deaths, healthcare professionals are in front of another crisis brought about by development and/or persistence of symptoms after the acute phase of SARS-CoV-2 infection (typically after 3 months), a condition conventionally called long-COVID 3 or post-COVID. 4 More than 100 symptoms can appear after a SARS-CoV-2 acute infection, affecting multiple systems, e.g., cardiovascular, respiratory, musculoskeletal, or neurological.…”
Section: Introductionmentioning
confidence: 99%
“…We will be pressing for this in the future along with measures to increase COVID-19 vaccine equity. African Governments and others need to ensure that healthcare professionals (HCPs) can readily administer COVID-19 vaccines to reduce future hospitalisations [ 103 , 104 ]. Increasing vaccinations will reduce infection rates and subsequent consequences including hospitalisations, thereby reducing unnecessary prescribing of antimicrobials and associated AMR [ 96 , 97 , 98 , 105 , 106 ].…”
Section: Introductionmentioning
confidence: 99%